The Steep Road to Institutionalizing Negotiable Governance in the Management of Village Development - Rahmad Hidayat; Hendra Hendra; Muhamad Iptidaiyah (Universitas Sultan Ageng Tirtayasa, 2019)
Law No. 6/2014 on Villages becomes the rule of application of negotiable governance in the management of village development. Authority in this domain must be translated as a negotiation space for various stakeholders. Accessibility of public participation in any regular citizenship forum must be guaranteed to be fulfilled by the Village Government, in line with the willingness of this village-scale authoritative institution to create public information transparency. This paper aims to examine the level of institutionalization of negotiable governance in the management of development in Bajo Village, Soromandi Sub-District, Bima District. As qualitative research with a descriptive approach, this research utilized in-depth interviews, observation, document tracking, and document analysis techniques in which a number of village government apparatus and villagers were used as informants to mine the data. The results of this study show that institutionalizing negotiable governance has not been taken seriously because the public participation in regular citizenship forums in Bajo Village is only possible because of